Producing Ceramic Water Purifiers Made Of Iraqi Bentonite Type (Bpl1) (Baghdad Science Journal, 2025)
In this study, ceramic purifier (CP) was produced from a mixture of Iraqi raw materials. This ceramic mixture was prepared using Bentonite as a Clay, Porcelanite as a Silica, and Limestone as a flux. The produced ceramic filter was formed by semi-dry compressing method and was fired at 1200 C?.Physical properties of the produced CP were measured. A hydraulic test rig was constructed to study the hydraulic conductivity of the produced CP. The average hydraulic conductivity of the produced CP was 55 times that of commercial types of ceramic filters.The mineral composition of the produced ceramics was found by X-Ray tests. Tests results showed that all of the produced ceramics filters composed mainly of low Cristobalte and Tridoymite in addition to some of other minerals.Both of the raw and the water purified by produced ceramic were tested for a number of water quality parameters. that the ceramic disc purifier could remove, as an average percentages of removal, 99.98% of turbidity, 78.86% of the electrical conductivity , 81.61% of the total dissolved solids, 73.45% of Ca++, 49.69% of Na+, 55.63% of NO3-, 37.54% of HCO3- . The results showed that CP has excellent adsorption ability for solutes of seven heavy metals, Mn, Fe, Pb, Cd, Co, Cu and Zn, at concentrations of 1 mg/leach and 10 mg/l each. The adsorption capacities of each filter to adsorb seven heavy metals were computed according to Langmuir model and Freundlich models. The results showed variety in adsorption capacities for each heavy metal.